PENDIDIKAN KEIMANAN SEBAGAI BASIS KECERDASAN SOSIAL PESERTA DIDIK: TELAAH PSIKOLOGI ISLAMI - Idi Warsah (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
This article aims to reveal the importance of faith in education as the basis of the Social intelligence of learners although it can not be measured concretely through quantitative data. This domain is a benchmark of the success of the educational process in Islam as the goal of Islamic education itself. This article use literature research, which examines the subject through the literature related to the focus of the problem that result the conclusion as follows: First, Man created by God was born as a person who brings potential social intelligence. The multi-dimensional social intelligence that God bestows on human beings is able to assume his duty as chalif and dedicate himself totally in the form of faith and piety to Allah; Secondly, the education of faith becomes important and the main thing is given to learners, by: introducing the name of Allah SWT and His Apostle; gives the description of ​​who the creator of the universe is through examply stories; introducing the Almighty of Allah SWT; to be an example for children in both worship and friendship; respect the abilities of the children; positioning them not as objects but as learning partners; and give a positive appreciation of all the advantages possessed by learners.